POLA NAFKAH GANDA MASYARAKAT NELAYAN IKAN NOMEI (Harpadon nehereus sp) DI JUATA LAUT KOTA TARAKAN KALIMANTAN UTARA - Tri Wuri Wijayanti; Qoriah Saleha; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2019)
The purpose of this study was to obtain a description of the dual livelihood patterns of fishermen families, to know the contribution of each family member of the Nomei fishermen who worked on family income and to know the motivation of fishermen's wives in Juata Laut who were involved in applying multiple livelihood patterns. The sampling method used was purposive sampling totaling 10 families consisting of nuclear families and extended families, each of 5 families in the Juata Laut Village. The results of this study indicate that the picture of the double income pattern applied by nuclear family members and extended families is still very limited. The types of work in the field of fisheries are carried out by men and women, where all men are generally fishermen and women are all processors of dried fish. The percentage of the contribution of husband's income to the nuclear family averaged 36.42% and the percentage contribution of wife's income was 63.58% on average. While the percentage of husband's income contribution to the broad family is an average of 28.39%, the percentage contribution of wife's income is an average of 51.76% and the contribution of other family income averages 19.85%. Motivation of the wives of fishermen who are involved in earning a living is dominant in the household income factor which is felt to be lacking.